2009
DOI: 10.1371/journal.pone.0007011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sequence and Structural Analyses of G-Protein-Coupled Receptor Crystal Structures and Implications for Molecular Models

Abstract: BackgroundUp until recently the only available experimental (high resolution) structure of a G-protein-coupled receptor (GPCR) was that of bovine rhodopsin. In the past few years the determination of GPCR structures has accelerated with three new receptors, as well as squid rhodopsin, being successfully crystallized. All share a common molecular architecture of seven transmembrane helices and can therefore serve as templates for building molecular models of homologous GPCRs. However, despite the common general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 83 publications
3
78
0
1
Order By: Relevance
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…Helical distortion and helix extension A number of helical features differentiate TMHs in the known structures (Worth et al 2009), including helix extensions (e.g., TMH5 and TMH6 in squid rhodopsin), Pro kink or distortion in TMH4, TMH5, TMH6, and TMH7 of most structures, Gly-Gly bulge/distortion (e.g., TMH2 of human or TMH1 of squid rhodopsins), and Gly bend (e.g., TMH3 of human rhodopsin). Some patterns of Pro in the TMH sequence lead to an insertion in the TMHs.…”
Section: Unger and Schertler 1995mentioning
confidence: 99%
“…Worth et al (2009) answered this question by analyzing in detail the sequence motifs and structural features that exist in the known structures and subsequently designing a flow diagram that allows modelers to chose the most relevant template structure, given the specific attributes observed in the query GPCR sequence. Another study has shown that using multiple templates to build a model slightly improves the resulting model (Mobarec et al 2009).…”
Section: Homology Modelingmentioning
confidence: 99%
“…Although the sequence similarity of these receptors is rather low (6), there are a few highly conserved residues in every transmembrane domain (TMD), and the three-dimensional arrangement of the TMDs is highly similar in all available crystal structures. These characteristics coupled with results from studies on conformational changes that occur during activation of different family A GPCRs suggest that they may share common activation mechanisms (7)(8)(9).…”
mentioning
confidence: 99%